Neonatal bacterial sepsis: risk factors, clinical features And short term outcome - Ibraheem, Mohammad f. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Neonatal infections are afrequent and important causes of neonatal morbidity and mortality especially in the developing countries. Objective: The aim of the study is to determine the clinical picture, risk factors associated with neonatal sepsis and to estimate short term outcome from neonatal sepsis and its relation to birth weight, gestational age, onset of sepsis and type of bacteria. Patients and Methods: A prospective study was conducted on 80 neonates presented with sepsis who had been admitted to intensive care unit in Children Welfare Teaching hospitals in Baghdad over six months period between (15th of January 2008 to 15th of June 2008).A thorough history and physical examination were carried out, and samples of blood were taken for blood culture and sensitivity. Results: Eighty neonates were studied, sepsis was confirmed by clinical and laboratory measures. Fifty five (68.7%) neonates were males and 25(31.2%) were females. Fifty four (67.5%) were preterm and 26 (32.5%) were full term. Fifty nine (73.25%) neonates were still alive during period of hospitalization and discharged home, while 21 (26.25%) neonates died. Early onset sepsis was detected in 26 (32.5%) neonates while late onset sepsis was detected in 54 (67.5%) neonates, However, the death rate was higher in early onset sepsis (57.7%) compared to late onset sepsis (18.5%). The death rate was higher in neonates with maternal history of prolonged rupture of membrane >18 hours (54.8%), also it was increased when there was fever or infection during pregnancy. Conclusions: The study showed that the most common neonatal risk factors that increase the incidence of mortality were early neonatal sepsis, home delivery, prolonged rupture of membrane more than 18 hours and maternal fever or infection, and the most common features were lethargy, absence or weak moro reflex and reluctant to feed, The most common bacteria isolated from blood cultures was E. coli.